2016
DOI: 10.1186/s12885-016-2358-2
|View full text |Cite
|
Sign up to set email alerts
|

Primary tumor site is a useful predictor of cetuximab efficacy in the third-line or salvage treatment of KRAS wild-type (exon 2 non-mutant) metastatic colorectal cancer: a nationwide cohort study

Abstract: BackgroundPrevious studies have shown left-sided colorectal cancer (LCRC) and right-sided colorectal cancer (RCRC) exhibit different molecular and clinicopathological features. We explored the association between the primary tumor site and cetuximab efficacy in KRAS wild-type colorectal cancer (CRC).MethodsThis study enrolled a cohort of patients, who had received cetuximab treatment after two or more lines of chemotherapy for KRAS wild-type (exon 2 nonmutant) metastatic CRC, from the databases of Taiwan Cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 30 publications
2
32
1
1
Order By: Relevance
“…The predictive value of primary tumor location in survival among patients with metastatic CRC was confirmed in several latest studies[2528]. Chen et al revealed that right-sided tumor site was an independent predictor of shorter PFS (HR = 1.32, P = 0.0072) and OS (HR = 1.45, P = 0.0003) among 969 patients with KRAS wild-type CRC receiving Cetuximab therapy treatment[26]. In agreement with it, Moretto et al’s study indicated that patients with right-sided RAS and BRAF wild-type metastatic CRC derived no benefit from single Cetuximab therapy (p<0.0001) [27].…”
Section: Discussionmentioning
confidence: 93%
“…The predictive value of primary tumor location in survival among patients with metastatic CRC was confirmed in several latest studies[2528]. Chen et al revealed that right-sided tumor site was an independent predictor of shorter PFS (HR = 1.32, P = 0.0072) and OS (HR = 1.45, P = 0.0003) among 969 patients with KRAS wild-type CRC receiving Cetuximab therapy treatment[26]. In agreement with it, Moretto et al’s study indicated that patients with right-sided RAS and BRAF wild-type metastatic CRC derived no benefit from single Cetuximab therapy (p<0.0001) [27].…”
Section: Discussionmentioning
confidence: 93%
“…The Role of Primary Tumor Sidedness: A growing body of data has shown that the location of the primary tumor can be both prognostic and predictive of response to EGFR inhibitors in metastatic CRC. [118][119][120][121][122][123][124][125] For example, outcomes of 75 patients with metastatic CRC treated with cetuximab, panitumumab, or cetuximab/irinotecan in first-line or subsequent lines of therapy at 3 Italian centers were analyzed based on sidedness of the primary tumor. 119 No responses were seen in the patients with rightsided primary tumors, compared with a response rate of 41% in those with left-sided primaries (P=.003).…”
Section: Cetuximab and Panitumumabmentioning
confidence: 99%
“…118,119,121,122 The panel believes that primary tumor sidedness is a surrogate for the nonrandom distribution of molecular subtypes across the colon and that the ongoing analysis of tumor specimens from the study will enable a better understanding of the biologic explanation of the observed difference in response to EGFR inhibitors. Until that time, only patients whose primary tumors originated on the left side of the colon (splenic flexure to rectum) should be offered cetuximab or panitumumab in the first-line treatment of metastatic disease.…”
Section: Cetuximab and Panitumumabmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypermethylation of the promoter regions of the ligands in CMS1 subtypes of CRC is demonstrated to be associated with the downregulation of some other genes. For instance, overexpressed epidermal growth factor receptor (EGFR) and insulin receptor substrate 2 are also known to occur in distal carcinomas particularly the CMS2 phenotype (K. H. Chen et al, 2016). CMS1 subgroup of CRC tumors displays a diffused immune infiltrate, expression of Th1 cytokines which is associated with good prognosis in CRC.…”
Section: Immune Responses and Immune Resistance In Crcmentioning
confidence: 99%